Qa-1b Modulates Resistance to Anti-PD-1 Immune Checkpoint Blockade in Tumors with Defects in Antigen Processing - Zhang, Xiao; Sabio, Erich; Krishna, Chirag; Ma, Xiaoxiao; Wang, Jingming; Jiang, Hui; Havel, Jonathan J; Chan, Timothy A (Molecular cancer research, 2021)
Immune checkpoint blockade (ICB) has improved cancer care, but ICB is only effective in some patients. The molecular mechanisms that influence ICB therapy response are not completely understood. The non-classical MHC class I molecule HLA-E and its mouse ortholog, Qa-1b, present a limited set of peptides in a TAP1-dependent manner to the NKG2A/CD94 heterodimer to transduce an inhibitory signal to natural killer (NK) and CD8+ T cells. However, deficiency of TAP1 allows Qa-1b to present an alternative peptidome to Qa-1b-restricted T-cell receptors of cytotoxic T cells. In this study, we used CRISPR-Cas9 to study the relationship between TAP1, Qa-1b, and response to anti-PD1 therapy. We hypothesized that immunotherapy response in TAP1-deficient tumors would be influenced by Qa-1b. Strikingly, using a syngeneic orthotopic mouse model, we found that although TAP1-deficient tumors were resistant to anti-PD1 treatment, anti-PD1 response was significantly enhanced in tumors lacking both TAP1 and Qa-1b. This increased sensitivity is partially dependent on NK cells. TAP1-deficient tumors were associated with an increase of intratumoral regulatory T cells (Treg) and neutrophils, whereas tumors lacking both TAP1 and Qa-1b exhibited an increased CD8+ T-cell to Treg ratio. These data suggest that direct inhibition of Qa-1b may alter the immune microenvironment to reverse resistance to anti-PD1 therapy, particularly in the context of antigen-processing defects. IMPLICATIONS: This study reveals important functional crosstalk between classical TAP-dependent MHC complexes and Qa-1b/HLA-E, particularly in tumors with impaired antigen-processing machinery. This can dramatically influence immunotherapy efficacy.Immune checkpoint blockade (ICB) has improved cancer care, but ICB is only effective in some patients. The molecular mechanisms that influence ICB therapy response are not completely understood. The non-classical MHC class I molecule HLA-E and its mouse ortholog, Qa-1b, present a limited set of peptides in a TAP1-dependent manner to the NKG2A/CD94 heterodimer to transduce an inhibitory signal to natural killer (NK) and CD8+ T cells. However, deficiency of TAP1 allows Qa-1b to present an alternative peptidome to Qa-1b-restricted T-cell receptors of cytotoxic T cells. In this study, we used CRISPR-Cas9 to study the relationship between TAP1, Qa-1b, and response to anti-PD1 therapy. We hypothesized that immunotherapy response in TAP1-deficient tumors would be influenced by Qa-1b. Strikingly, using a syngeneic orthotopic mouse model, we found that although TAP1-deficient tumors were resistant to anti-PD1 treatment, anti-PD1 response was significantly enhanced in tumors lacking both TAP1 and Qa-1b. This increased sensitivity is partially dependent on NK cells. TAP1-deficient tumors were associated with an increase of intratumoral regulatory T cells (Treg) and neutrophils, whereas tumors lacking both TAP1 and Qa-1b exhibited an increased CD8+ T-cell to Treg ratio. These data suggest that direct inhibition of Qa-1b may alter the immune microenvironment to reverse resistance to anti-PD1 therapy, particularly in the context of antigen-processing defects. IMPLICATIONS: This study reveals important functional crosstalk between classical TAP-dependent MHC complexes and Qa-1b/HLA-E, particularly in tumors with impaired antigen-processing machinery. This can dramatically influence immunotherapy efficacy.